Nghiên cứu tổng hợp biodiesel từ nguyên liệu dầu vi tảo bằng quá trình hai giai đoạn sử dụng hệ xúc tác axit-bazơ rắn - Thành, Nguyễn Trung; Diệu Hồng, Nguyễn Khánh; Ngọ, Đinh Thị (Vietnam Journal of Chemistry, 2014)
This report covered a two-stage biodiesel synthesis process by using acid-base catalysts consisting of SO42-/ZrO2 and Ca(NO3)2/SiO2. A micro-algal oil typed Botryococcus having a very high content of free fatty acids (FFAs) was used as feedstock. In the first stage, a major amount of FFAs was converted to fatty acid methyl esters (FAMEs) on the solid acid catalyst SO42-/ZrO2. The product of this process including FAMEs and triglycerides became the feedstock for the second stage reactions; in which they was completely transesterified to FAMEs on a solid base catalyst Ca(NO3)2/SiO2. The conditions for the reactions were investigated to reach the optimum parameters for whole biodiesel synthesis. Keywords: Biodiesel, calcium nitrate, zirconia, microalgae oil, Botryococcus.